PEMANFAATAN ASAP CAIR ALANG-ALANG (Imperata cylindrica) SEBAGAI PENGAWET TERHADAP KARAKTERISTIK BUAH PISANG MAKAU (Musa spp.) - Dian Fitriarni; Rafika Ayuni (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Research on the utilization of liquid smoke especially for preservation of fruit has been done and become one of alternative methods that can be used to maintain fruit shelf life. Liquid smoke raw materials can come from a variety of sources one of which comes from the Alang-alang (Imperata cylindrica). This study aims to determine the ability of liquid smoke made from alang-alang as a preservative of bananas and to know the effect on the characteristics of bananas. The sample used in this research is a local banana known as Pisang Makau (Musa spp). This research uses experimental method with 7 days of storage time. Initial stages of the research are cleaning the fruit, dyeing, drying, and storage at room temperature. This research uses liquid smoke from alang-alang by using 2 various concentrations 50% and 100%. The next stage is the analysis of the characteristics of bananas such as color, fruit texture, fruit weight, sugar content, and vitamin C levels. Based on the analysis results obtained by Pisang Makau with the treatment of liquid has a longer shelf life than the control. Based on the results of the analysis of the shelf life of fruit treated with liquid smoke decreased levels of sugar and vitamin C levels. Percentage decrease levels of sugar and vitamin C between the fruit with the treatment and control not much different. This shows that liquid smoke from alang-alang has the ability to retain the shelf life of bananas without affecting sugar and vitamin C levels in bananas in this case for Pisang Makau. Levels of sugar and vitamin C in bananas decreased during the process of storage and bunding of fruit